Integration of artificial intelligence (AI) technology in teaching and learning to build resilient character - Asep Deni Normansyah Asep; Darda Abdullah Sjam; Cep Miftah Khoerudin (Jurnal Konseling dan Pendidikan, 2025)
The development of artificial intelligence (AI) in the 21st century has had a transformative impact on the world of education, particularly in higher education. AI offers great potential for improving the effectiveness and personalisation of learning, but at the same time raises ethical and moral challenges in shaping student character. This study aims to analyse how the integration of AI in the learning process contributes to strengthening the resilient character of students—covering moral, ethical, and professional dimensions—in the midst of the digital transformation era. The method used is a qualitative literature review with a systematic approach, analysing 30 scientific articles from reputable national (SINTA 1–2) and international (Scopus/DOAJ) journals published between 2015 and 2025. The analysis was conducted thematically to identify the benefits, challenges, and pedagogical strategies in the application of AI in higher education. The results of the study revealed four main themes: (1) AI increases student learning autonomy, personalisation, and intrinsic motivation; (2) ethical risks arise in the form of plagiarism, algorithmic bias, and a decline in moral reflection; (3) significant challenges lie in infrastructure gaps, technological literacy, and lecturers' pedagogical readiness; and (4) effective strategies require a humanistic approach and ethical education policies that position teachers as facilitators of values. In conclusion, AI has the potential to strengthen students' moral, ethical, and professional resilience when integrated reflectively and based on human values. These findings have significant implications for the development of higher education policies that strike a balance between technological innovation and character education in the digital age.